2016
DOI: 10.1111/ina.12304
|View full text |Cite
|
Sign up to set email alerts
|

Indoor mold levels and current asthma among school-aged children in Saskatchewan, Canada

Abstract: Current knowledge regarding the association between indoor mold exposures and asthma is still limited. The objective of this case-control study was to investigate the relationship between objectively measured indoor mold levels and current asthma among school-aged children. Parents completed a questionnaire survey of health history and home environmental conditions. Asthma cases had a history of doctor-diagnosed asthma or current wheeze without a cold in the past 12 months. Controls were age- and sex-matched t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 48 publications
1
29
1
1
Order By: Relevance
“…In addition, visible mold in bedrooms and basements in participants' homes were associated with persistent asthma and colds (16.8%, p < 0.0001). Other fungal studies conducted in Europe, Canada, and Australia have also found similar results [45,57,58]. Viral exposure also plays a critical role in the development of asthma and asthma morbidity [9, 11•].…”
Section: Endotoxinsupporting
confidence: 55%
See 2 more Smart Citations
“…In addition, visible mold in bedrooms and basements in participants' homes were associated with persistent asthma and colds (16.8%, p < 0.0001). Other fungal studies conducted in Europe, Canada, and Australia have also found similar results [45,57,58]. Viral exposure also plays a critical role in the development of asthma and asthma morbidity [9, 11•].…”
Section: Endotoxinsupporting
confidence: 55%
“…This suggests a dose-dependent relationship between mold exposure and asthma severity [44]. This finding is supported by Oluwole et al [45], who demonstrated that high mold levels in children's play areas are associated with current asthma (adjusted OR = 3.0, 95% CI (1.11-8.0)). Furthermore, additional studies have demonstrated that sensitization to Alternaria increases with higher mold concentration exposure and may lead to a risk of hospitalization, especially in the urban setting [46][47][48][49].…”
Section: Endotoxinmentioning
confidence: 56%
See 1 more Smart Citation
“…Supporting this, a birth cohort study demonstrated that exposure to moisture damage and visible mold in early infancy were associated with asthma development [29]. More specific measurement of mold exposure yielded similar findings as Oluwole et al [30] documented that mold levels in dust samples from both play area floors and bedroom mattresses were significantly associated with current asthma. In a meta-analysis, increased levels of Penicillium , Aspergillus , Cladosporium , and Alternaria species were associated with increased exacerbation of current asthma symptoms in children [31].…”
Section: Mold Exposure and Asthmamentioning
confidence: 65%
“…Benign indoor environments are the habitats of bacteria, viruses, and fungi . Among the different kinds of microbes, fungi represent a heterogeneous group that play an important role in human pathology . Health symptoms of fungal exposure include but are not limited to allergies, infection, and inflammation .…”
Section: Introductionmentioning
confidence: 99%